PEMBELAJARAN BAHASA ARAB TOPIK ‘ADAD MA’DŪD MELALUI HIBRIDISASI YOUTUBE DAN QUIZIZZ PADA GENERASI DIGITAL NATIVE - Nazrailman, Alqan; Sopian, Asep; Khalid, Shofa Musthofa (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Learning Arabic, especially the topic of 'Adad Ma'dud,' faces challenges in student comprehension and motivation, especially among the digital native generation. This research applies a qualitative descriptive method approach with field observations to elaborate on the implementation of learning through the hybridization between the digital media YouTube and Quizizz as digital learning media among students at SMK-IT Daarussyifa. The research results demonstrate the importance of the teachers role in implementing Arabic language learning especially the topic of ‘Adad Ma’dud, by utilizing digital media that combines YouTube and Quizizz. Students' perspectives on the hybridization of YouTube and Quizizz are highly positive, showing enthusiasm and better understanding of the material when compared to without using the hybridization of the two media. The majority of students were able to overcome technical challenges and enjoyed using both media in learning. Apart from that, students' learning outcomes also significantly improve after implementing of media hybridization. Therefore, learning Arabic, especially the topic ‘Adad Ma’dud through the hybridization of YouTube and Quizizz proves to be an effective solution for enhancing student comprehension and motivation, especially among the digital native generation.